Interference of Commelina benghalensis in the initial growth of Eucalyptus grandis in winter and summer - Fontoura Costa, Augusto Guerreiro; Bacha, Allan Lopes [UNESP]; Pires, Rodrigo Neto; Morelli Damasceno Pavani, Maria do Carmo [UNESP]; Costa Aguiar Alves, Pedro Luis da [UNESP] (Centro Pesquisas Florestais, Ufsm, 2021)
Eucalyptus seedlings are sensitive to the interference imposed by weed community, especially during the initial growth period, which is the first year after crop establishment. Thus, this study aimed at evaluating the effect of increasing densities of Commelina benghalensis L. on the initial growth of Eucalyptus grandis Hill (ex Maiden) plants at two seasons of the year. For this, two experiments were carried out using 70 L boxes in an open and semi-controlled area: one in winter (during 90 days) and another in summer (during 120 days). Both experiments were randomized block designs with four replicates each. The treatments consisted of increasing densities of tropical spiderwort, namely: 0 (control), 4, 8, 16, 20, 28, 36, 40, 60 and 80 plants m(-2). Fifteen days after planting the tropical spiderwort seedlings, one seedling of eucalyptus was planted in the center of each box. The height, diameter, leaf area and total dry mass of eucalyptus were evaluated at the end of the experimental periods. Densities from 4 plants m(-2) negatively interfered with eucalyptus growth, reducing by 38.4% the leaf area and 35% the dry mass in winter. While in summer, we found reductions of 52.9% in the leaf area and 64.7% in the dry mass. We concluded that the density from 4 plants m(-2) interferes with the growth of eucalyptus and that the weed shows a more aggressive competitive behavior in the summer causing greater interference in the eucalyptus.
Keywords: Eucalypt; Tropical spiderwort; Competition; Weeds; Weed densities